Application of Cooperative Learning Model Type Make A Match to Improve Students' Learning Outcomes in Junior High School Baiturrahim Jambi City - Devie Novallyan; Reni Anggraini; Nanang Nofriadi (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
This study is discusses about the implementation model of learning cooperative type make a match on the subjects of Natural Sciences (IPA) Integrated, especially in grade VIIIA students of Baiturrahim Junior High School Jambi City. The purpose of this research is to know the application of cooperative learning model type make a match can help improve students' learning results in Natural Science lessons in grade VIII Baiturrahim Junior High School Jambi City. This research uses Class Action Research which consists of four stages in each cycle namely planning, action, observation and reflection. As for the data on the increase in the percentage of learning completion: before the implementation of learning research by applying the make a match (Pre cycle) model, the number of students who achieved learning completion was the number of 8 students (38.1%). Then after the percentage of learning completed in cycle I learning increased to 15 students (71.4%), cycle II increased to 20 students (95,23%). From these results can be concluded that the application of cooperative models of make a match type can improve students' learning outcomes in human digestive system materials and gastrointestinal tract.